2012
DOI: 10.1371/journal.pone.0031962
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking of High Avidity HER-2/neu-Specific T Cells into HER-2/neu-Expressing Tumors after Depletion of Effector/Memory-Like Regulatory T Cells

Abstract: BackgroundCancer vaccines are designed to activate and enhance cancer-antigen-targeted T cells that are suppressed through multiple mechanisms of immune tolerance in cancer-bearing hosts. T regulatory cell (Treg) suppression of tumor-specific T cells is one barrier to effective immunization. A second mechanism is the deletion of high avidity tumor-specific T cells, which leaves a less effective low avidity tumor specific T cell repertoire available for activation by vaccines. Treg depleting agents including lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 70 publications
3
61
0
Order By: Relevance
“…This suggests direct crosstalk between the tumor cells and Treg cells. Consistent with the large body of studies showing that Treg cells are strong promoters of breast cancer progression and metastasis, anti-CD25 antibody-mediated Treg blockade or depletion leads to a stronger antitumor immune response and better clinical outcomes (Rech et al, 2012;Weiss et al, 2012). Together, these studies suggest that the Treg cell is a potent negative regulator of anti-tumor immune responses and represents an attractive therapeutic target in breast cancer.…”
Section: T Regulatory (Treg) Cellssupporting
confidence: 63%
“…This suggests direct crosstalk between the tumor cells and Treg cells. Consistent with the large body of studies showing that Treg cells are strong promoters of breast cancer progression and metastasis, anti-CD25 antibody-mediated Treg blockade or depletion leads to a stronger antitumor immune response and better clinical outcomes (Rech et al, 2012;Weiss et al, 2012). Together, these studies suggest that the Treg cell is a potent negative regulator of anti-tumor immune responses and represents an attractive therapeutic target in breast cancer.…”
Section: T Regulatory (Treg) Cellssupporting
confidence: 63%
“…In addition, several preclinical studies have shown that Tregs might help to maintain immune tolerance and restrain vaccine-induced tumor immunity by controlling suboptimal rather than high-affinity TCR-bearing T cells (41,42). Together with a recent report on the ability of cyclophosphamide to enhance the trafficking of highavidity CTLs to tumor sites (43), this evidence suggests that cyclophosphamide should favor the expansion of highavidity CTLs in a peptide-vaccine setting. Regarding the use of low-dose IL-2, we deliberately chose the "late" administration schedule (i.e., 3 months after the beginning of vaccination) based on a previous report by Slingluff and colleagues that showed a beneficial effect with such a schedule compared with that of early IL-2 administration for the induction of T-cell responses by a multipeptide melanoma vaccine (16).…”
Section: Discussionmentioning
confidence: 82%
“…Patients and experimental models with cancer showed that Treg cells down-regulated the activity of effector function against tumors, resulting in T-cell dysfunction in cancerbearing hosts (Weiss et al, 2012;Sakuishi et al, 2013). An increased population of Treg cells was reported in patients with ovarian cancer (Wicherek et al, 2011), lung cancer (Erfani et al, 2012), and breast cancer (Decker et al, 2012).…”
Section: Introductionmentioning
confidence: 99%